PICOSECOND TIME-RESOLVED STUDY OF THE LUMINESCENCE OF CD1-XMNXTE IN MAGNETIC-FIELDS - Wong, K; Hayes, W; Ryan, J; Ramdas, A (1987)
Picosecond time-resolved photoluminescence studies have been made at temperatures down to 1.8 K and in magnetic fields of up to 8 T of the dilute magnetic semiconductor Cd1-xMnxTe for x=0.09, 0.2 and 0.3. The dynamics of lattice-disorder-induced and magnetically induced localisation of excitons is discussed. © 1987 IOP Publishing Ltd.